Politics and Karate: Historical Influences on the Practice of Goju-ryu - Giles Hopkins (Universidad de León, 2012)
The 1936 "masters meeting" sponsored by the Ryukyu Newspaper Company-a gathering of karate masters, journalists, and government leaders-gives us some indication of the political realities at play in Japan in the early decades of the 20th century and how they may have affected Okinawan karate. Tradition often seems as though it is a safeguard against change. However, the reality is that a resurgence of nationalism fed an anti-Chinese bias and an effort to assimilate Okinawan culture; both affected karate. With economic hardships in Okinawa and a desire to popularize karate, traditions did change. Some teachers sought ways to preserve traditional Okinawan martial arts within this changing political landscape. But at what cost?